Data structures & problem solving using Java - Weiss, Mark Allen (Pearson/Addison-Wesley, 2006)
Data Structures and Problem Solving Using Java 3/e provides a practical introduction to data structures from a viewpoint of abstract thinking and problem solving, and incorporates the enhancements of Java 5.0. It includes coverage of generic programming, and content on the design of generic collection classes. This book is appropriate for readers who are familiar with basic Java programming concepts or are new to the language and want to learn how it treats data structures concepts.